Intensive Mothering in British Columbia: Understanding the Impact of an “Investing-in-Children” Framework on Mothering Ideology - Butler, Kate (International Journal of Canadian Studies / Revue internationale d’études canadiennes)

(untitled) (Conseil international d’études canadiennes, 2010)
In our contemporary era, policy frameworks privilege the idea that children should be the target of government intervention in the family. Jane Jenson calls this the “investing-in-children” framework, as children, rather than parents, are supposedly at the forefront of government involvement in family life. This is a shift from an earlier “family responsibility” framework in which parents were held responsible for their child’s well-being (Jenson 173). However, the “investing-in-children” framework actually continues to place much responsibility on the shoulders of parents while at the same time creating mechanisms for their further regulation. In this paper, the author explores the relationship between intensive mothering ideology and an “investing-in-children” policy framework. Motherhood (particularly for those at the margins of society) is reconceptualized as a private, individual experience. The BC government’s commitment to an “investing-in-children” framework is captured in the 2008 document, Strong, Safe and Supported. This publication captures the ways in which parental regulation is achieved through a strategy of government policy promoting the well-being of BC’s children. Although the community is supposedly implicated in the welfare of its children, it is clear that parental responsibility is the main subject of further regulation.